Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jcb.29468
|View full text |Cite
|
Sign up to set email alerts
|

FASTKD2 promotes cancer cell progression through upregulating Myc expression in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most fatal cancers of the digestive system. Despite the development of novel therapeutic methods, including chemotherapy, radiotherapy, and molecular targeted therapy, the incidence rate of PDAC is almost equal to the mortality rate with 5-year overall survival rate less than 5%. Kras mutation is found in 95% of patient with PDAC specimens, but targeting Kras mutation do not benefit patients with pancreatic cancer in preclinical trials. c-Myc is one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Other studies have suggested additional links between FASTKD2 and disease. A study found an association between dysregulated FASTKD2 and poor prognosis of patients with pancreatic ductal adenocarcinoma, through FASTKD2's role in promoting tumor growth and invasion, via upregulation of c-Myc expression [174]. Furthermore, RNA sequencing identified FASTKD2 as one of several mitochondria-related differentially expressed transcripts in astrocytes from patients with Alzheimer's disease, although no further characterization or validation were conducted [160].…”
Section: Functional Partners Of Pseudouridine Transferasesmentioning
confidence: 99%
“…Other studies have suggested additional links between FASTKD2 and disease. A study found an association between dysregulated FASTKD2 and poor prognosis of patients with pancreatic ductal adenocarcinoma, through FASTKD2's role in promoting tumor growth and invasion, via upregulation of c-Myc expression [174]. Furthermore, RNA sequencing identified FASTKD2 as one of several mitochondria-related differentially expressed transcripts in astrocytes from patients with Alzheimer's disease, although no further characterization or validation were conducted [160].…”
Section: Functional Partners Of Pseudouridine Transferasesmentioning
confidence: 99%
“…In addition, MYC oncoprotein expression is thought to be related to the output of major cellular processes including proliferation, apoptosis, differentiation, and metabolism [25]. An increasing number of studies have reported that some genes promote cancer progression by activating the MYC pathway [28][29][30]. For example, LCAT3 plays an oncogenic role in lung cancer by binding to FUBP1 to activate MYC [31].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of FASTKD4 lung cancer cells led to the inhibition of cell proliferation, migration, and invasion highlighting its role in tumour growth in lung cancer [ 23 ]. In the case of pancreatic adenocarcinoma, FASTK and FASTKD2 had also been involved in proliferation, invasion, and migration and hence poor prognosis [ 24 , 25 ]. Conversely, the overexpression of FASTKD3 in bladder cancer improved patient survival [ 26 ].…”
Section: Implication Of Fastk Family In Cancersmentioning
confidence: 99%